2021
DOI: 10.1002/cti2.1307
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 pathway in active large vessel vasculitis patients with a poor prognosis: a longitudinal transcriptome analysis

Abstract: Objectives. Large vessel vasculitis (LVV) is characterised by a high relapse rate. Because accurate assessment of the LVV disease status can be difficult, an accurate prognostic marker for initial risk stratification is required. We conducted a comprehensive longitudinal investigation of next-generation RNA-sequencing data for patients with LVV to explore useful biomarkers associated with clinical characteristics. Methods. Key molecular pathways relevant to LVV pathogenesis were identified by examining the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…However, it remains unclear how the other types of inflammatory cells in the peripheral blood contribute to the progression and development of TA. Kotaro found that IL-1 pathway expression was elevated in the peripheral blood of patients with refractory large vessel vasculitis by analyzing bulk-seq data, but the author failed to elucidate the relationship between the IL-1 pathway and different types of immune cells ( Matsumoto et al, 2021 ). Compared with bulk-seq, scRNA-seq technology can analyze the transcriptome in each cell type, which provides more comprehensive information on the function of different inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear how the other types of inflammatory cells in the peripheral blood contribute to the progression and development of TA. Kotaro found that IL-1 pathway expression was elevated in the peripheral blood of patients with refractory large vessel vasculitis by analyzing bulk-seq data, but the author failed to elucidate the relationship between the IL-1 pathway and different types of immune cells ( Matsumoto et al, 2021 ). Compared with bulk-seq, scRNA-seq technology can analyze the transcriptome in each cell type, which provides more comprehensive information on the function of different inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study firstly performed bulk RNA-sequencing of TA vessel tissues to obtain the overall alterations of transcriptome in TA. Regarding the materials used for TA research, most studies detected RNA, cytokines, chemokines by using peripheral blood samples ( Matsumoto et al, 2021 ; Qing et al, 2021 ; Kabeerdoss et al, 2022 ; Kong et al, 2022 ). In this way, several susceptibility locus have been identified by genome-wide association studies to pinpoint potential clues for new therapeutic targets ( Renauer et al, 2015 ; Ortiz-Fernández et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of IL1R1 and IL1R2 IHC staining confirmed these bioinformatic analysis. Examined the whole blood RNA and draw a conclusion that IL-1 signaling pathway related to the advanced stage of disease and a poor prognosis ( Matsumoto et al, 2021 ). IL-1 and IL1R may be a potential target of TA treatment, in which further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether this would affect neutrophil function. 321 The soluble pattern recognition 1 receptor pentraxin 3, which is involved in vascular injury, is upregulated in GCA as in other types of vasculitis. 322 Taken together, these results provide proof of concept that neutrophils may participate in the pathogenesis of GCA.…”
Section: Giant Cell Arteritis: Miscommunication Between Different Neu...mentioning
confidence: 99%
“…Whether this affects neutrophil function remains to be elucidated. 321 Interestingly, anti-endothelial cell antibodies have been reported in TAK, although their role in pathophysiology remains unclear. 343,344 The major histological difference observed on the vascular wall in TAK compared to GCA is the thickening of the adventitia.…”
Section: Takayasu Arteritis: When Neutrophils Participate In Arterial...mentioning
confidence: 99%